PROFILE OF ALPHA TOCOPHEROL (VITAMIN E) AND OIL LEVELS IN MUNG BEAN SPROUTS (VIGNA RADIATA (L.) R. WILCZEK) - Zainy Azhar, Ghanes
Mung bean is one of legumes widely cultivated in Asia as a food source and a source of Vitamin E (?-tocopherol). This study aimed to determine ?-tocopherol content in mung bean and its correlation to the oil contained in mung bean. ?-Tokoferol extraction was carried out us by sonication method using methanol solvent by R100% conditions at 40oC temperature for 30 minutes. Determination of ?-Tocopherol contents was carried out using high performance liquid chromatography (HPLC) with UV-Vis detector. Mung bean ?-Tocopherol content on germination for 0, 24, 48, and 72 hours were 1,432±0,16; 1,657±0,25; 1,719±0,15; dan 1,816±0,66 mg/g. Furthermore, the oil content was determined using soxhlet extraction using n-hexane as solvent at 70oC for ±2 hours. Mung bean oil content on germination for 0, 24, 48, and 72 hours were 2.846 ± 0.319; 2.539 ± 0.429; 2.304 ± 0.193; and 1.694 ± 0.092%. There was no significant difference in ?-tocopherol contents from the four samples, but the oil content decreased as germination time goes by (up to 72 hours).